An 82-m 9 Gb/s PAM4 FSO-POF-UWOC Convergent System - Chung-Yi Li; Hai-Han Lu; Yun-Chieh Wang; Zhen-Han Wang; Chung-Wei Su; Yi-Feng Lu; Wen-Shing Tsai (IEEE Photonics Journal)
With the increasing demand for free-space/underwater environmental monitoring, disaster precaution, and manufacturing industry applications, free-space optical (FSO)-plastic optical fiber (POF)-underwater wireless optical communication (UWOC) convergence is designed to be a promising framework for providing long-haul free-space with underwater links. An 82-m 9 Gb/s four-level pulse amplitude modulation (PAM4) FSO-POF-UWOC convergent system employing a 405-nm blue-light injection-locked laser diode (LD) is thereby offered and practically demonstrated. Results reveal that a 1.8-GHz 405-nm blue-light injection-locked LD can be effectively applied for a 9-Gb/s PAM4 signal transmission over 50-m FSO link, 30-m graded-index (GI)-POF transportation, and 2 m clear ocean underwater channel. To the authors’ understanding, this study is the first to practically build an 82-m 9 Gb/s PAM4 FSO-POF-UWOC convergent system that effectively constructs a long-haul optical wireless-wired-wireless link using doublet lenses, GI-POF, and optical beam reducer. The performances of the proposed convergent systems are analyzed by bit error rate and non-return-to-zero eye diagram in real-time over an 82-m transport. This framework is the leading one to establish a long-haul FSO-POF-UWOC convergent system with qualified transmission performances. It guides a promising way to facilitate wide applications in the convergence of FSO, POF, and UWOC.